Hepatic serum amyloid A1 upregulates interleukin‐17 (IL‐17) in γδ T cells through Toll‐like receptor 2 and is associated with psoriatic symptoms in transgenic mice. (4th April 2019) - Choi, Minjee; Kim, Myoung Ok; Lee, Jinhee; Jeong, Jain; Sung, Yonghun; Park, Song; Kwon, Wookbong; Jang, Soyoung; Park, Si Jun; Kim, Hyeng‐Soo; Jang, Woo Young; Kim, Sung Hyun; et al.
Abstract: Serum amyloid A (SAA) is an acute phase protein with pro‐inflammatory cytokine‐like properties. Recent studies have revealed that SAA promoted interleukin‐17 (IL‐17) production by various cells, including γδ T cells. γδ T cells are innate immune cells and express Toll‐like receptor 2 (TLR2) on their surface, which is one of the SAA receptors. In this study, we investigated the relationship between γδ T cells and SAA1 through TLR2, by using hepatic SAA1‐overexpressing transgenic (TG) mice. By injecting CU‐CPT22, which is a TLR2 inhibitor, into the mice, we confirmed that SAA1 induced IL‐17 in γδ T cells through TLR2. In vitro studies have confirmed that SAA1 increased IL‐17 secretion in γδ T cells in combination with IL‐23. We also observed a thickened epidermis layer and granulocyte penetration into the skin similar to the pathology of psoriasis in TG mice. In addition, strongly expressed SAA1 and penetration of γδ T cells in the skin of TG mice were detected. The exacerbation of psoriasis is associated with an increase in IL‐17 levels. Therefore, these symptoms were induced by IL‐17‐producing γδ T cells increased by SAA1. Our study confirmed that SAA1 was a prominent protein that increased IL‐17 levels through TLR2 in γδ T cells, confirming the possibility that SAA1 may exacerbate inflammatory diseases through γδ T cells.